Mother Infant Retention for Health (MIR4Health): Study Design, Adaptations, and Challenges With PMTCT Implementation Science Research. (1st August 2016) - Fayorsey, Ruby N.; Chege, Duncan; Wang, Chunhui; Reidy, William; Peters, Zachary; Syengo, Masila; Barasa, Chrisostim; Owino, Samuel O.; Sirengo, Martin; Hawken, Mark P.; Abrams, Elaine J.
Abstract : Background: Effective retention of HIV-infected mothers and their infants is fraught with multiple challenges, resulting in loss across the continuum of prevention of mother-to-child HIV transmission (PMTCT) care and missed opportunities to offer life-saving HIV prevention and treatment. Methods: The Mother Infant Retention for Health study is an individual-randomized study evaluating the effectiveness of active patient follow-up compared with standard of care on the combined outcome of attrition of HIV-infected women and their infants at 6 months postpartum. Lay counselors administered the active patient follow-up package of interventions, including individualized health education, use of flip charts during clinic visits, and at home, phone and short message service appointment reminders, active phone and physical tracking of patients immediately after missed clinic visits, and individualized retention and adherence support. Results: Use of study visits to indicate participant progression along the PMTCT cascade highlights the nature of loss among women and infants in PMTCT care because of issues such as pregnancy complications, infant deaths, and transfer out. Delay in implementation of Option B+, unanticipated slow enrollment, a health-care worker strike, rapid HIV test kit shortages, and changes in national PMTCT guidelines necessitated several modifications to the protocol design and implementation to ensure successful completion of the study. Conclusions: Flexibility when operationalizing an implementation science study is critical in the context of the shifting landscape in a noncontrolled "real-world" setting. Trial Registration: Clinicaltrials.gov NCT01962220.